Citizen Security and Social Media in Mexico"„¢s Public Sphere - Blandford, Kristen; D'Amour, Rosemary (Virtualis, 2013)
With the rise of drug-related violence in Mexico, Mexican citizens are using social media to warn fellow citizens and promote intra-national communication. This research focuses on the public sphere as it relates to selected social media platforms including Twitter, Facebook and blogs"€appropriate platforms because social media is transforming the public sphere in Mexico, moving conversations from offline to online. The researchers do not focus on one single social or political movement. Instead, the focus is on the broader issue of citizen security in Mexico, how it is being discussed in the public sphere, and how this is changing the public sphere. With the increase in drug-related violence since 2006, people are obtaining and sharing information about citizen security in Mexico through information and communication technologies. Access to social media (Facebook, Twitter, blogs, etc.) is transforming the public sphere as various sectors (civil society, media and the government) figure out how to engage people and create niche networks on these various platforms. The decentralized nature of citizen security and disruptions in traditional communication channels are forcing citizens to seek information and discuss these issues online.